Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: the importance of private collections - Carolin Haug; Jelle W. F. Reumer; Joachim T. Haug; Antonio Arillo; Denis Audo; Dany Azar; Viktor Baranov; Rolf Beutel; Sylvain Charbonnier; Rodney Feldmann; Christian Foth; René H. B. Fraaije; et al. (PalZ, 2020)

Comment on the letter of the Society of Vertebrate Paleontology (SVP) dated April 21, 2020 regarding “Fossils from conflict zones and reproducibility of fossil-based scientific data”: Myanmar amber - Joachim T. Haug; Dany Azar; Andrew Ross; Jacek Szwedo; Bo Wang; Antonio Arillo; Viktor Baranov; Julia Bechteler; Rolf Beutel; Vladimir Blagoderov; Xavier Delclòs; Jason Dunlop; et al. (PalZ, 2020)

A new Triassic decapod, Platykotta akaina, from the Arabian shelf of the northern United Arab Emirates: earliest occurrence of the Anomura - Jérôme Chablais; Rodney M. Feldmann; Carrie E. Schweitzer (PalZ, 2011)

Gondwanan radiation of the Southern Hemisphere crayfishes (Decapoda: Parastacidae): evidence from fossils and molecules - Alicia Toon; Marcos Pérez‐Losada; Carrie E. Schweitzer; Rodney M. Feldmann; Michael Carlson; Keith A. Crandall (Journal of Biogeography, 2010)
Aim The sequential break‐up of Gondwana is thought to be a dominant process in the establishment of shared biota across landmasses of the Southern Hemisphere. Yet similar distributions are shared by taxa whose radiations clearly post‐date the Gondwanan break‐up. Thus, determining the contribution of vicariance versus dispersal to seemingly Gondwanan biota is complex. The southern freshwater crayfishes (family Parastacidae) are distributed on Australia and New Guinea, South America, Madagascar and New Zealand and are unlikely to have dispersed via oceans, owing to strict freshwater limitations. We test the hypotheses that the break‐up of Gondwana has led to (1) a predominately east–west (((Australia, New Zealand: 80 Ma) Madagascar: 160–121 Ma) South America: 165–140 Ma), or (2) a southern (((Australia, South America: 52–35 Ma) New Zealand: 80 Ma) Madagascar: 160–121 Ma) pattern for parastacid crayfish. Further, we examine the evidence for a complete drowning of New Zealand and subsequent colonization by freshwater crayfish. Location Southern Hemisphere. Methods The evolutionary relationships among the 15 genera of Parastacidae were reconstructed using mitochondrial [16S, cytochrome c oxidase subunit I (COI)] and nuclear (18S, 28S) sequence data and maximum likelihood and Bayesian methods of phylogenetic reconstruction. A Bayesian ( multidivtime ) molecular dating method using six fossil calibrations and phylogenetic inference was used to estimate divergence time among crayfish clades on Gondwanan landmasses. Results The South American crayfish are monophyletic and a sister group to all other southern crayfish. Australian crayfish are not monophyletic, with two Tasmanian genera, Spinastacoides and Ombrastacoides , forming a clade with New Zealand and Malagasy crayfish (both monophyletic). Divergence of crayfish among southern landmasses is estimated to have occurred around the Late Jurassic to Early Cretaceous (109–178 Ma). Main conclusions The estimated phylogenetic relationships and time of divergence among the Southern Hemisphere crayfishes were consistent with an east–west pattern of Gondwanan divergence. The divergence between Australia and New Zealand (109–160 Ma) pre‐dated the rifting at around 80 Ma, suggesting that these lineages were established prior to the break‐up. Owing to the age of the New Zealand crayfish, we reject the hypothesis that there was a complete drowning of New Zealand crayfish habitat.